Hyaluronic acid-based nano drug delivery systems for breast cancer treatment: Recent advances - Jia, Yufeng; Chen, Siwen; Wang, Chenyu; Sun, Tao; Yang, Liqun (Frontiers in Bioengineering and Biotechnology, 2022)
Breast cancer (BC) is the most common malignancy among females worldwide, and high resistance to drugs and metastasis rates are the leading causes of death in BC patients. Releasing anti-cancer drugs precisely to the tumour site can improve the efficacy and reduce the side effects on the body. Natural polymers are attracting extensive interest as drug carriers in treating breast cancer. Hyaluronic acid (HA) is a natural polysaccharide with excellent biocompatibility, biodegradability, and non-immunogenicity and is a significant component of the extracellular matrix. The CD44 receptor of HA is overexpressed in breast cancer cells and can be targeted in breast tumours. Therefore, many researchers have developed nano-drug delivery systems (NDDS) based on HA's CD44 receptor tumour-targeting properties. This review examines the application of HA in NDDSs for breast cancer in recent years. Based on the structural composition of NDDSs, they are divided into HA NDDSs, Modified HA NDDSs, and HA hybrid NDDSs.